2021
DOI: 10.1016/j.trre.2020.100588
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in solid organ transplant recipients: A systematic review and meta-analysis of current literature

Abstract: Severe acute respiratory virus syndrome 2 (SARS-CoV-2) has led to a worldwide pandemic. Early studies in solid organ transplant (SOT) recipients suggested a wide variety of presentations, however, there remains a paucity of robust data in this population. We conducted a systematic review and meta-analysis of SOT recipients with SARS-CoV-2 infection from January 1 st t October 9 th , 2020. Pooled incidence of symptoms, treatments and outcomes were assessed. Two hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
208
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(229 citation statements)
references
References 127 publications
15
208
3
3
Order By: Relevance
“…As recent meta-analyses have focused exclusively on cancer 136 or SOT patients. 137 Herein, results show differences among the immunocompromised and general population cohorts after COVID-19. First, SOT patients with COVID-19 had more comorbidities (cardiovascular disease, diabetes, and hypertension), dyspnea and required intensive care more often, and had higher mortality despite having similar disease severity versus the general population with COVID-19.…”
Section: Discussionmentioning
confidence: 76%
“…As recent meta-analyses have focused exclusively on cancer 136 or SOT patients. 137 Herein, results show differences among the immunocompromised and general population cohorts after COVID-19. First, SOT patients with COVID-19 had more comorbidities (cardiovascular disease, diabetes, and hypertension), dyspnea and required intensive care more often, and had higher mortality despite having similar disease severity versus the general population with COVID-19.…”
Section: Discussionmentioning
confidence: 76%
“…Upon SARS-CoV-2 infection, lung-transplanted pwCF were more frequently symptomatic, were admitted to hospital 1.7-fold more frequently and required intensive care 8-fold more frequently than pwCF without lung transplant. Previous studies also found that solid organ transplant recipients require more treatment and medical care upon SARS-CoV-2 infection, whether transplant was for CF [ 5 , 7 ] or other reasons [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early on, acute phase reactants and systemic cytokines were implicated in patient outcomes 46 and hospital stay and mortality were decreased by dexamethasone 47 , suggesting that an excessive host immune response might contribute to COVID-19 mortality. However, there were also indications that inadequate host immunity might contribute to adverse COVID-19 outcomes, including the association of lymphopenia with mortality as well as the potentially inferior outcomes of patients on chronic immunosuppression, such as patients with autoimmune diseases or organ transplant recipients [48][49][50][51] . Recent studies defined immune signatures associated with severe COVID-19, including activated CD4, CD8 T cells, plasmablasts, and robust antibody responses 15,16,20,52 .…”
Section: Discussionmentioning
confidence: 99%